Pengaruh Brand Equity Terhadap Keputusan Pembelian Saus Sambal Merek Abc Pada Masyarakat Desa Tanah Abang Kecamatan Batang Hari Leko - Anggraini, Sasti; Nofiawaty; Hamdaini, Yulia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of brand equity on purchasing decisions at ABC chili sauce brand at Tanah Abang village, Batang Hari Leko sub-district. This research is a quantitative research with a survey method. The data used in this study using essential data and additional information. The sampling technique in this study used accidental sampling technique. Data was collected through online questionnaire using Google Forms to 97 respondents. This study used multiple linear analysis techniques, simultaneous tests (F test), and partial tests (t test). The results of this study indicate that brand equity has a significant positive effect partially or simultaneously on purchasing decisions. The results of multiple linear regression tests show that brand association has a dominant influence on purchasing decisions at ABC chili sauce brand in Tanah Abang village, Batang Hari Leko sub-district.